Primary Versus Preoperative Radiation for Locally Advanced Vulvar Cancer. Issue 4 (May 2017) - Natesan, Divya; Hong, Julian C.; Foote, Jonathan; Sosa, Julie A.; Havrilesky, Laura; Chino, Junzo
Abstract : Objectives: The objective of this study was to evaluate patterns of care and the survival impact of primary radiation and preoperative radiation therapy with surgery in women with locally advanced vulvar cancer using a large national cohort. Methods and Materials: Women with vulvar cancer, diagnosed from 2004 to 2012, who received primary or preoperative radiation therapy were identified in the National Cancer Database. Patient characteristics, such as age, race, American Joint Committee on Cancer stage, and comorbidity score, were compared between those that received primary radiation only and those that received preoperative radiation with surgery using the χ 2, Fisher exact, and Mann-Whitney tests as appropriate. Overall survival (OS) by treatment approaches was estimated via the Kaplan-Meier method and compared using the log-rank test. Factors associated with OS were determined using univariate and multivariate Cox proportional hazards regression models. Results: A total of 2046 women were identified; 1407 of these women (69%) received primary radiation therapy (RT; n = 421) or chemoradiation therapy (CRT; n = 986) (RT/CRT), and 639 women (31%) received preoperative RT (n = 92) or CRT (n = 547) followed by surgery (RT/CRT + S). The American Joint Committee on Cancer staging distributions were as follows: T1 (n = 152), T2 (n = 1436), T3 (n = 405), N0 (n = 899), N1 (n = 480), N2 (n = 445), and N3 (n = 40). Median follow-up was 21.9 months. Primary RT/CRT was associated with compromised OS, compared with preoperative RT/CRT + S (41.7% vs 57.1% at 3 years, respectively; P < 0.001). On multivariate analysis, OS associated with primary RT/CRT with doses more than 55 Gy was not significantly different from RT/CRT + S (hazards ratio, 1.139; 95% confidence interval, 0.969–1.338; P = 0.116). Use of concurrent chemotherapy improved OS of primary RT with doses more than 55 Gy compared with CRT + S (hazards ratio, 1.107; 95% confidence interval, 0.919–1.334; P = 0.234). Conclusions: In a large nationwide analysis, primary nonsurgical management of vulvar cancer with RT was associated with compromised survival compared with preoperative RT with surgery. However, with doses more than 55 Gy and concurrent chemotherapy, nonoperative approaches had comparable survival compared with preoperative CRT + S.